Qualitative research in journalism : taking it to the streets - Iorio, Sharon Hartin, 1943- (LEA's communication series., 2004)
This volume highlights the integration of qualitative research methods into traditional journalism, offering new ways of expanding and enhancing news coverage. Designed for readers without prior experience in social science research, this collection presents a wide variety of qualitative techniques and their applications in journalistic practice. The work brings together contributions from professional journalists and journalism scholars who are highly experienced in conducting qualitative research. These experts demonstrate how valid, reliable qualitative procedures can be used to increase co.